MEMINIMALKAN SISWA UNDERACHIEVERS MELALUI OPTIMALISASI KECERDASAN EMOSIONAL PADA SISWA KELAS V SEKOLAH DASAR - , Sugiyo (Pendidikan Dasar, 2009)
Abstract; The study aimsi is minimazing students underachiement by optimizing their emotional intelligence in the teaching process of the fifth graders of Petompon Elementary schools 05, 06, and 07 Semarang.The study used was the Classroom Action Recearch made up of two cycles:  cycle one and cycle two. With the on following results:  at cycles I 16 students performance accordance with their respective potential.Then  in cycle II from 15 students underachievers decreases 11 students or 11 student achieved minimal grade, while 4 student did not. It can be means that by optimizing the students emotional intellegence, underachieveers can be minimized.